Roles of hypoxia, stem cells and epithelial–mesenchymal transition in the spread and treatment resistance of head and neck cancer. (7th May 2015) - Gammon, Luke; Mackenzie, Ian C.
Abstract : Evidence from a wide range of studies indicates that hypoxia and the resulting cellular changes that are induced by HIF‐1α lead to transcriptional up‐regulation of a diversity of genes that play major roles in modifying the cellular behaviour of head and neck squamous cell carcinoma (HNSCC). Although the mechanisms of cell adaptation to hypoxia are still not entirely clear, many studies relate hypoxia to enhanced survival of malignant cells. Stronger staining of tissue sections for HIF‐1α correlates with poor prognostic outcomes, and the hypoxic tumour microenvironment generates selective pressures that enhance the ability of cancer stem cells (CSCs) to evade therapeutically induced cell death. The ability of hypoxia to further increase the resistance of CSCs to conventional therapeutics, whether they act by induction of apoptosis, senescence or autophagy, appears to limit therapeutic effectiveness of current agents. The demonstration of hypoxic induction of phenotypic changes leading to a subpopulation of CSCs with high motility, greater invasive properties and yet greater therapeutic resistance, complicates the issue still further. It appears that therapeutic interventions that allow manipulation of HIF‐1α levels and responses, whether induced by hypoxia or by other mechanisms, could provide more effective actions of chemo‐ and radiotherapies at lower therapeutic dosages and thus result in better control of tumours with less toxicity to patients.